Soluble forms of PD-L1 and PD-1 as prognostic and predictive markers of sunitinib efficacy in patients with metastatic clear cell renal cell carcinoma. (1st January 2020) - Montemagno, Christopher; Hagege, Anais; Borchiellini, Delphine; Thamphya, Brice; Rastoin, Olivia; Ambrosetti, Damien; Iovanna, Juan; Rioux-Leclercq, Nathalie; Porta, Camillio; Negrier, Sylvie; Ferrero, Jean-Marc; Chamorey, Emmanuel; et al.
ABSTRACT: Metastatic clear cell renal cell carcinoma (mccRCC) benefits from several treatment options in the first-line setting with VEGFR inhibitors and/or immunotherapy including anti-PD-L1 or anti-PD1 agents. Identification of predictive biomarkers is highly needed to optimize patient care. Circulating markers could reflect the biology of metastatic disease. Therefore, we evaluated soluble forms of PD-L1 (sPD-L1) and PD-1 (sPD-1) in mccRCC patients. The levels of sPD-L1 and sPD-1 were evaluated from plasma samples of mccRCC patients before they received a first-line treatment (T0) by the VEGFR inhibitor sunitinib (50 patients) or by the anti-VEGF bevacizumab (37 patients). The levels of sPD-L1 and sPD-1 were correlated to clinical parameters and progression-free survival (PFS). High levels of sPD-1 or sPDL1 were not correlated to PFS under bevacizumab while they were independent prognostic factors of PFS in the sunitinib group. Patients with high T0 plasmatic levels of sPD-L1 had a shorter PFS (11.3 vs 22.5 months, p = .011) in the sunitinib group. Equivalent shorter PFS was found with high levels of sPD-1 (8.6 vs 14.1 months, p = .009). mccRCC patients with high plasmatic levels of sPD-L1 or sPD-1 are poor responders to sunitinib. sPD-L1 or sPD-1 could be a valuable tool to guide the optimal treatment strategy including VEGFR inhibitor.